2016
DOI: 10.1002/art.39646
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Arthritis in KRN T Cell Receptor–Transgenic Mice Does Not Require Interleukin‐17 or Th17 Cells

Abstract: Objective Th17 cells and interleukin (IL)-17 cytokine family members are implicated in the pathogenesis of many rheumatic diseases. Most studies of mouse models of inflammatory arthritis have demonstrated a key role for the pro-inflammatory cytokine IL-17A and its receptor, the IL-17 receptor (IL-17R) A/C heterodimer. Using a rigorous genetic approach, we evaluated the contribution of Th17 cells and IL-17 in the autoantibody-dependent, KRN T cell receptor (TCR) transgenic mouse model of arthritis. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Furthermore, Ono et al clearly demonstrate that while IL-17A stimulates osteoblastogenesis of precursor cells from long bone repair tissue, it does the opposite in calvarial osteoblasts. 5 It is surprising that arthritis symptoms were not modulated in the study by Shaw et al , 14 as it has previously been reported that genetic IL-17A deficiency 17 or IL-17A antibody-mediated neutralisation 18 suppresses arthritic disease in the same model. This aspect was not discussed by the authors but does warrant further investigation.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Ono et al clearly demonstrate that while IL-17A stimulates osteoblastogenesis of precursor cells from long bone repair tissue, it does the opposite in calvarial osteoblasts. 5 It is surprising that arthritis symptoms were not modulated in the study by Shaw et al , 14 as it has previously been reported that genetic IL-17A deficiency 17 or IL-17A antibody-mediated neutralisation 18 suppresses arthritic disease in the same model. This aspect was not discussed by the authors but does warrant further investigation.…”
Section: Discussionmentioning
confidence: 92%
“…Tfh17 cells are also expanded in KBN mice under the control of the microbiome ( 26 ). Recent studies have shown that Th17 cells are dispensable for the development of disease ( 27 ) and that the gut microbiome regulates KBN Tfh but not Th17 cells ( 28 ). Moreover, the analysis of K/BxN IL-21-VFP.IL-17A-GFP mice directly showed a robust expansion of IL-21-producing CD4 + T cells but very few IL-17-procuding CD4 + T cells (Roopenian, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an influential study by Wu et al published in 2010 demonstrated that the generation of arthritogenic antibodies in the K/BxN mouse model of arthritis was mediated by Th17 cells, and that these cells were in turn dependent on colonization with segmented filamentous bacteria (SFB), a commensal inhabitant of the mouse terminal ileum. In contrast, in this issue of Arthritis & Rheumatology , Auger et al report that interleukin‐17A (IL‐17A) is not required for the formation of arthritogenic antibodies in this model, and neither are SFB. Similar findings showing that IL‐17A was “dispensable” for K/BxN mouse arthritis were reported by other investigators .…”
mentioning
confidence: 82%